A46 THE INFLAMMATORY CASPASES COORDINATE MUCOSAL RESTRICTION OF SALMONELLA THROUGH THE EPITHELIAL-INTRINSIC INFLAMMASOME AND IL-22 DRIVEN MUCIN SECRETION. (26th February 2020) - Crowley, S M; Allaire, J M; Han, X; Graef, F A; Stahl, M; Knodler, L; Vallance, B
Abstract: Background: Intestinal epithelial cells (IECs) are located at the interface between the gut lumen and the underlying mucosal defense system. Here, they play a central role in the coordination of intestinal homeostasis, tempering pro-inflammatory responses but remaining rapidly responsive to noxious stimuli such as enteric pathogens. One early response mechanism by which IECs engage in immune defense is through the activation of the inflammasome which mobilizes the inflammatory caspases; caspase-1 and -11. Aims: Here, we investigated the role of the inflammasome in overall mucosal defense against the enteric pathogen Salmonella enterica serovar Typhimurium. Methods: Streptomycin-pretreated C57BL/6 (wildtype), Casp1/11 deficient (−/−), Casp1−/− and Casp11−/− mice were orally infected with Salmonella and burdens determined in intestinal tissues at 18h post infection (p.i.). Results: Increased pathogen loads were observed for all caspase-deficient mice compared to wildtype, which correlated with increased IEC intracellular Salmonella burdens. Interestingly, despite increased bacterial loads, pathology scores for all inflammatory caspase mice were decreased, especially with regard to 'IEC damage' and 'goblet cell loss'. To determine if the increased burdens were due to the loss of IEC-intrinsic inflammasomes, enteroid monolayers were derived and infected with Salmonella . This revealed significantly increased intracellular burdens in caspase-deficient monolayers as compared to wildtype, in concert with a marked decrease in IEC shedding and cell death. Peak inflammatory caspase activity was displayed in shedding wildtype IECs, suggesting the IEC-intrinsic inflammasome restricts Salmonella infection through infected IEC expulsion. The role of inflammasome signaling in acute mucosal defense was also examined. Wildtype tissue demonstrated a dramatic increase in mucus thickness (as evaluated by Muc2 immunostaining) and antimicrobial Reg3γ and β lectin transcript levels compared to caspase-deficient mice. Mucin release and Reg3 induction has been previously linked to IL-22, therefore we measured IL-22 expression and observed increased secretion in infected wildtype mice compared to Casp1/11−/−. This correlated with increased cecal infiltration of IL-22 producing ILC3 and NK T-cells. When infected mice were treated with IL-22 neutralizing antibody, this increased Salmonella burdens and decreased infection-induced mucus secretion, while no differences were observed in Casp1/11−/− treated with neutralizing antibody or isotype control. Conclusions: Therefore the intestinal epithelium utilizes inflammasome signaling to coordinate multiple layers of innate defense at the gut mucosal surface to ultimately restrict enteric pathogen infections and their systemic spread. Funding Agencies: CCC, CIHR, NRCUBC